Photothermal/photodynamic antibacterial hydrogel embedded with copper carbon dots and Au nanoparticles - Ju Lv; Yuheng Qiu; Lang Pan; Xinyue Zhang; Mengting Li; Xueqiong Yin (Nano TransMed, 2024)
In this paper, we created a hydrogel (named AuNPs-CuCCDs@Gel) with photothermal and photodynamic performance through incorporating copper carbon dots (CuCCDs) and Au nanoparticles (AuNPs) into gelatin and chitosan hydrogels. The thus-obtained hydrogel exhibited a high photothermal and photodynamic antibacterial activity with a superior singlet oxygen yield (0.70), which was better than that of methylene blue (0.52). After laser irradiation at 808 nm for 6 min, the temperature of AuNPs-CuCCDs@Gel rose from room temperature to 50 °C, which manifested good effects for avoiding local heat damage and protecting normal cells. AuNPs-CuCCDs@Gel exhibited the highest antibacterial efficacy of 96.46% and 97.48% against S. aureus and E. coli respectively. The significantly improved bactericidal performance was attributed to the synergistic effects of hyperthermia and reactive oxygen species (ROS). This work suggests that photothermal/photodynamic antibacterial hydrogel is a promising agent for treating wound infection.